The Rho Termination Factor of Clostridium botulinum Contains a Prion-Like Domain with a Highly Amyloidogenic Core - Pallarès, Irantzu; Iglesias, Valentin; Ventura, Salvador (Frontiers in Microbiology, 2016)
Prion-like proteins can switch between a soluble intrinsically disordered conformation and a highly ordered amyloid assembly. This conformational promiscuity is encoded in specific sequence regions, known as prion domains (PrDs). Prions are best known as the causative factors of neurological diseases in mammals. However, bioinformatics analyses reveal that proteins bearing PrDs are present in all kingdoms of life, including bacteria, thus supporting the idea that they serve conserved beneficial cellular functions. Despite the proportion of predicted prion-like proteins in bacterial proteomes is generally low, pathogenic species seem to have a higher prionic load, suggesting that these malleable proteins may favor pathogenic traits. In the present work, we performed a stringent computational analysis of the Clostridium botulinum pathogen proteome in the search for prion-like proteins. A total of 54 candidates were predicted for this anaerobic bacterium, including the transcription termination Rho factor. This RNA-binding protein has been shown to play a crucial role in bacterial adaptation to changing environments. We show here that the predicted disordered PrD domain of this RNA-binding protein contains an inner, highly polar, asparagine-rich short sequence able to spontaneously self-assemble into amyloid-like structures, bearing thus the potential to induce a Rho factor conformational switch that might rewire gene expression in response to environmental conditions.